Performance analysis and effect of pandemic condition on utility grid connected PV system - Battula, Veera Vasantha Rao; Krishnarao, Padmavathi (Institute of Advanced Engineering and Science, 2024)
In this research paper effect of pandemic and performance analysis of the utility grid connected PV system under net metering is evaluated for one years based on PV plant generation data. The performance of the system depends on annual average final yield, reference yield, and array yield and their values are 3.87 kWh kWp-1. d-1, 4.57 kWh kWp-1. d-1, and 4.29 7kWh kWp-1d-1 the performance ratio and capacity utilization factor are 77.48% and 15.68%. Due to pandemic campus energy consumption is less so energy export to grid is more than the energy import from grid. As per the state energy policy minimum billing is done even the export units are more than the imported units which result in increase in return on investment (ROI) compared to post pandemic. The above statistics illustrate the quite strong performance of solar power plants built in the Indian state of the Andhra Pradesh, Guntur.